Phlorotannins from Brown Algae (Fucus vesiculosus) Inhibited the Formation of Advanced Glycation Endproducts by Scavenging Reactive Carbonyls - Liu, Haiyan; Gu, Liwei (Journal of agricultural and food chemistry, 2012)
Accumulation of advanced glycation end products (AGEs) in vivo is associated with aging, diabetes, Alzheimer’s disease, renal failure, etc. The objective of this study was to investigate the inhibitory effects of brown algae Fucus vesiculosus phlorotannins on the formation of AGEs. F. vesiculosus phlorotannins were extracted using 70% acetone. The resultant extract was fractionated into dichloromethane, ethyl acetate, butanol, and water fractions. The ethyl acetate fraction was further fractionated into four subfractions (Ethyl-F1 to -F4) using a Sephadex LH-20 column. F. vesiculosus acetone extract or fractions significantly inhibited the formation of AGEs mediated by glucose and methylglyoxal in a concentration-dependent manner. The concentrations of F. vesiculosus extracts required to inhibit 50% of albumin glycation (EC50) in the bovine serum albumin (BSA)–methylglyoxal assay were lower than those of aminoguanidine (a drug candidate for diabetic complication), except for F. vesiculosus acetone extract and dichloromethane fraction. In the BSA–glucose assay, F. vesiculosus extracts inhibited BSA glycation more than or as effectively as aminoguanidine, except for Ethyl-F3 and -F4. The ethyl acetate fraction and its four subfractions scavenged more than 50% of methylglyoxal in two hours. The hypothesis whether F. vesiculosus phlorotannins scavenged reactive carbonyls by forming adducts was tested. Phloroglucinol, the constituent unit of phlorotannins, reacted with glyoxal and methylglyoxal. Five phloroglucinol–carbonyl adducts were detected and tentatively identified using HPLC–ESI-MS n .